The level of including indicators of sustainable development goals in Omani's social studies texbooks (5-12) - Al-Habsi, Najah Salim; Al-Rabaani, Ahmed Hamad (Journal of Curriculum and Teaching Methodology, 2025)
The study investigated the level of including indicators of sustainable development goals in Omani social studies textbooks (5-12). A Delphi methodology was used to define the indicators that should be included in these books through (17) experts and specialists. Also, context analysis methodology was used to analyze)18(social studies textbooks (2023-2024) through content analysis cards consisting of (17) goals and (51) indicators. The results showed that the total frequency of indicators of sustainable development goals in all social studies textbooks was (845).The highest frequency was related to the goal of “sustainably manage forests, combat desertification, and halt and reverse land degradation and halt biodiversity loss” by (17.7%). And the least inclusion was an indicator of the “reducing inequality within and among countries” by (0.4%). The results also found that textbook of Economic Geography had the highest percentage of inclusion (20.7%) while textbooks of Islamic civilization had the lowest percentage (0.7%). The study recommended enhancing the inclusion of indicators that had a low level of inclusion to foster the contribution of social studies in raising individual awareness of sustainable development.
Keywords: sustainable development indicators; social studies textbooks; Oman